Fabrication and Characterization of Gliclazide Loaded Microcapsules - Asad,Muhammad (2014)
This study aimed to formulate, characterize and evaluate the Gliclazide (GLZ) microcapsules prepared with sodium alginate, guar gum and pectin in different ratios by ionotropic-gelation method. The microcapsules were evaluated against different parameters such as particle size and shape, Carr's index, Hausner's ratio, rheological studies and drug release kinetics. Fourier Transform Infra Red (FTIR) and Differential Scanning Calorimetric (DSC) studies demonstrated the absence of any drug - polymers interaction. Promising characteristics were observed in rheological behavior and release kinetics. The size of microcapsules and percentage yield was in the range of 676 to 727 µm and 69 to 77%, respectively. Scanning electron micrographs revealed that microcapsules were discrete, spherical and free flowing. Entrapment efficiency and uniform drug release kinetics were some of the probable characteristics depicting the novel formulation design of Gliclazide microcapsules.